Variations in Intraocular Pressure Following Photorefractive Keratectomy in Different Degree of Myopia at Dr Yap Eye Hospital - Mufida Dwi Nurhayati; Suhardjo Suhardjo (Majalah Oftalmologi Indonesia, 2015)
Backgorund: To investigate the variations in intraocular pressure following PRK in different degree of myopia.Methods: Restrospective cohort study of 315 patients (429 eyes) who underwent photorefractive keratectomy at Yap Eye Hospital between January 2011 and December 2012. Visual acuity, refractive status, and intraocular pressure were examined before, 2, 4, 8, 12 weeks after photorefractive keratectomy. IOP was measured directly using non-contact tonometry and calculated using Chang’s formula (ΔP = -0.12 x refractive change – 1.36 mmHg). Variations in IOP were assessed comparing follow-up to baseline IOP.Results: There were 225 men and 90 women with mean age 22,9 years. Overall, compared to IOP prior surgery (mean 15.6mmHg), there were significant variations in measured IOP at 2, 4, 8, and 12 weeks after the procedures (variations were -30-.6% (mean 11.0mmHg), -25.0% (11.7mmHg), -26.3 (mean 11.5mmHg), -29.5% (mean 11.0mmHg) consecutively; p for variations<0.001). However, these variations were also presents in low, moderate, and high myopia (all p for variations <0.001). However, there were almost none variations using converted IOP (overall -9.14% (14.9mmHg); low myopia -8.91% (14.3mmHg); moderate myopia -5.81% (14.6mmHg); high myopia 0% (15.5mmHg); p<0.01).Conclusion: PRK caused relatively decreased variations in measured IOP, however, with converted IOP these variations are very small (relatively no difference in pre and postoperative IOP).